A Bibliography of Littleton's Tenures as an Archetype for the Study of Early English Legal Printing. Issue 1 (2nd January 2018) - Lind, Douglas W.
Abstract: For hundreds of years, bibliographies have been invaluable tools for researchers, collectors, and institutions, to provide contextual understanding as well as adding depth to collections. In this piece, the author uses his updated bibliography of the first 200 years of Littleton's Tenures to examine many aspects of early English legal printing. These include the development and evolution of the content of early legal materials, as well economic and other factors driving the market for printed law books. Preceding the bibliography is a list of fundamental bibliographic terms concerning early printing, contextually applied to Littleton's Tenures .